Persepsi Guru Tentang Pengaruh Kepemimpinan Kepala Sekolah, Iklim Organisasi Dan Tunjangan Sertifikasi Terhadap Kinerja Guru (Studi Kasus : Guru Di Smp 3 Imogiri Kabupaten Bantul) - Retno Yuli Astuti (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2014)
The study aims to determine the performance of employees using three indicators which include teachers' perception of principal leadership, school organizational climate, and teacher certification benefits. Teachers' perception of the principal leadership was measured from the leader's capability to develop a sense of group togetherness, teamwork, group motivation, problem solving, decision making, and inter-member conflict resolution. The leader's ability to help improve efficiency for the purpose of role specialization, organizational activities, resource accumulation, and group preparedness to face the changes and crises, leader's ability to improve the quality of work life, to develop subordinates' confidence, to improve subordinates' skills, to help develop and prosper the subordinates' psychology. As for the variable of organizational climate, it was measured using the indicators of structure, responsibility, risk, reward and punishment, and warmth and support. Teacher certification benefit was measured from students' attitude toward and view on 10 assessments of teachers' professional experience. The variable of teachers' can be measured from their capability of planning and preparing instruction, their mastery of the subject matter to be delivered, mastery of instructional method and strategy, assignments distributed to the students, classroom management skills, and assessment and evaluation skills. The sample consisted of all teachers of SMP 3 Imogiri, Bantul. Quantitative data analysis was conducted using multiple regression technique and a qualitative analysis. The results demonstrated that teachers' perception of principal leadership has a positive and significant effect on the performance of the teachers of SMP 3 Imogiri, Bantul Regency. Further, school organizational climate was also found to have a positive and significant effect on the performance of the teachers of SMP 3 Imogiri, Bantul. Teacher certification benefit was also found to have a positive and significant effect on the performance of the teachers of SMP 3 Imogiri, Bantul. The magnitude of influence of teachers' perception of the principal leadership, school organizational climate, teacher certification benefits amount to 0.861 or 86.1%. This means that teachers' performance was influenced by those three variables; teachers' perception of the principal leadership, school organizational climate, and teacher certification benefits by 86.1% while the remaining 13.9% was influenced or explained by variables other than those employed by the author. The variable with most positive influence on the teachers' performance was the teachers' perception of the principal leadership that amount to 4.926.